Enhancing the Antibiofilm Activity of β-1,3-Glucanase-Functionalized Nanoparticles Loaded With Amphotericin B Against Candida albicans Biofilm - Tan, Yulong; Ma, Su; Ding, Ting; Ludwig, Roland; Lee, Jintae; Xu, Jiaman (Frontiers in Microbiology, 2022)
Candida biofilm related infections cause an increased morbidity and mortality in patients with a reduced immune response. Traditional antifungal therapies prove not enough with the biofilm matrix acting as a perfusion barrier. Thus, novel methods are required to improve drug delivery and kill the Candida inside the biofilm. In this study, Amphotericin B (AmpB)-loaded chitosan nanoparticles (CSNP), which was functioned with β-1,3-glucanase (Gls), were fabricated (CSNP-AmpB-Gls) and their antibiofilm activity was evaluated against Candida albicans biofilm in-vitro. Scanning electron microscopy and confocal laser scanning microscopy were employed to examine the biofilm architecture and cell viability. CSNP-AmpB-Gls inhibited planktonic cell growth and biofilm formation effectively and exhibited the highest efficacy on disruption of mature biofilm than free AmpB or CSNP-AmpB. The created nanoparticles proved to penetrate the biofilm so as to interfere with cells inside directly and disassemble the biofilm matrix. CSNP-AmpB-Gls was able to eradicate the clinical isolates biofilms as well. These results suggest the potential applicability of CSNP-AmpB-Gls for treatment of Candida biofilm related infections.